2022
DOI: 10.1021/acsaelm.2c00781
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyimide Nanofiber-Based Triboelectric Nanogenerator for Harvesting Energy at Elevated Temperatures

Abstract: The thermionic emission effect and the destruction of the polymer surface structure caused by elevated temperatures severely affect the electron transfer in triboelectric nanogenerator (TENGs); thus, previous studies on the performance of polymer-based TENGs at elevated temperatures have mainly focused on that below 200 °C. Polyimide (PI) with high thermal stability and excellent triboelectric negativity has been widely used in the TENG but lacks systematic investigation in high-temperature environments. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The TENG could retain 68% of its output after burning for 60 s. Again, electrospun polyimide mats have also been used as flame retardant TENGs. 112 The performance of such a device was found to decrease with an increase in temperature. It could retain around 25.48% of the voltage and 23% of the current output values even at 250 °C.…”
Section: Functional Tengsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TENG could retain 68% of its output after burning for 60 s. Again, electrospun polyimide mats have also been used as flame retardant TENGs. 112 The performance of such a device was found to decrease with an increase in temperature. It could retain around 25.48% of the voltage and 23% of the current output values even at 250 °C.…”
Section: Functional Tengsmentioning
confidence: 99%
“…The power density of the wood based TENG could reach 24.2 mW/m 2 . The TENG could retain 68% of its output after burning for 60 s. Again, electrospun polyimide mats have also been used as flame retardant TENGs . The performance of such a device was found to decrease with an increase in temperature.…”
Section: Functional Tengsmentioning
confidence: 99%
“…In addition, researchers have successfully incorporated polymers such as PVDF, [ 99 ] polyvinylpyrrolidone (PVP), [ 100 ] PI, [ 101 ] and nylon [ 102 ] into nanofibers by the electrostatic spinning process. Zheng et al [ 35 ] reported the fabrication of a vertical contact‐separation TENG by adopting an electrospun PVDF membrane and nylon nanowires (Figure 4c).…”
Section: Selection and Optimization Of Triboelectric Materialsmentioning
confidence: 99%
“…Other than the above progress (the comparison is shown in Table 2 ), the following works are also of great significance. The PI nanofibers prepared by Shi et al [ 22 ] using electrospinning technology and assembled in TENG can be used at an ultra-high temperature of 250 °C with exceptional output performance. By introducing dynamic disulfide bond exchange and flexible PDMS fragments into the PI main chain, Li et al [ 54 ] endow PI with a self-healing property, providing theoretical guidance for the production of self-healing TENG.…”
Section: Applications Of Pi In Sensorsmentioning
confidence: 99%
“…In addition to the commonly used PI films, PI foams, PI fibers, PI aerogels, and so on have also been prepared. Above all, porous PI aerogels and PI fibers are used as the tribo-contact layer of triboelectric nanogenerators (TENG) and can greatly improve the performance of TENG [ 20 , 21 , 22 ]. On account of the triboelectrification and energy harvesting (EH) benefits of TENG, it can be used for the testing of embedded applications, especially those involving self-powered sensors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%